Antidepressant-like effects of ginsenoside Rg5 in mice: Involving of hippocampus BDNF signaling pathway. (3rd April 2017) - Xu, Dawei; Wang, Chengniu; Zhao, Wei; Gao, Shengfeng; Cui, Zhiming
Highlights: Ginsenoside Rg5 has antidepressant-like effects in mice and may be developed as a new antidepressant. Ginsenoside Rg5 has enhancing effects on the hippocampal BDNF system, extending its pharmacological effects. Ginsenoside Rg5 has no effects on the serotonin system. Abstract: Ginsenoside Rg5 is one of the major bioactive ingredients of Panax ginseng with little toxicity and has been shown to have pharmacological effects on the central nervous system. In this study, we investigated the antidepressant effects of Rg5 in mice models of depression. The effects of Rg5 were first assessed in the forced swimming test (FST) and tail suspension test (TST), and then investigated in the chronic social defeat stress (CSDS) model of depression. The changes in hippocampal brain-derived neurotrophic factor (BDNF) signaling pathway after CSDS and Rg5 treatment were also examined. The tryptophan hydroxylase inhibitor and tyrosine kinase B inhibitor were used to explore the antidepressant mechanisms of Rg5. It was found that Rg5 exhibited antidepressant-like activities in the FST and TST without affecting locomotor activity. Rg5 was also effective in the CSDS model of depression, and restored the CSDS-induced decrease in hippocampal BDNF signaling cascade. Moreover, the usage of the tyrosine kinase B inhibitor blocked the antidepressant effects of Rg5, while the tryptophan hydroxylase inhibitor did not. Collectively, ginsenoside Rg5 has antidepressant activities via the activation of hippocampal BDNF system.